Self-medication among nursing students at a private university in southern Minas Gerais (Research, Society and Development, 2021)
Due to the easy way for the people to acquire some classes of medicines, without the need for a medical prescription and, under the influence of harmful stimuli from the media, self-medication has become a common conduct that poses serious risks to the population's health and quality of life. This study analyzed the frequency of self-medication among nursing students at a university in southern Minas Gerais, Brazil. A semi-structured questionnaire on self-medication was applied to students in 2018. Among 110 respondents, from 17 to 46 years of age, there was a predominance of females (78.18%) in the age group between 20-30 years. There was a high frequency of students who reported the practice of self-medication (94.5%), including for prescription medicines and, being this habit, more common among students from the last periods of the course. The reuse of prescriptions and medications from previous treatments was also common. The health problems most reported by the interviewees that led to self-medication were as following: headache (87.20%), flu and colds (82.7%), fever (55.4%), allergies (52.7%) and infections/inflammations (46.3%). The most used medicine classes were as following: analgesics/antipyretics (86.3%), flu/medicines to treat colds (84.5%), syrups (82.7%), anti-inflammatories (74.5%) and antiallergics/antihistamines (56.3%). It is concluded that the frequency of self-medication among nursing students is high, with this habit being more common among students from the last periods of the course.